Diagnosis and empirical treatment of fever of unknown origin (FUO) in adult neutropenic patients: guidelines of the Infectious Diseases Working Party (AGIHO) of the German Society of Hematology and Medical Oncology (DGHO) - Heinz, W. J.; Buchheidt, Dieter (Annals of hematology, 2017)
Fever may be the only clinical symptom at the onset of infection in neutropenic cancer patients undergoing myelosuppressive chemotherapy. A prompt and evidence-based diagnostic and therapeutic approach is mandatory. A systematic search of current literature was conducted, including only full papers and excluding allogeneic hematopoietic stem cell transplant recipients. Recommendations for diagnosis and therapy were developed by an expert panel and approved after plenary discussion by the AGIHO. Randomized clinical trials were mainly available for therapeutic decisions, and new diagnostic procedures have been introduced into clinical practice in the past decade. Stratification into a high-risk versus low-risk patient population is recommended. In high-risk patients, initial empirical antimicrobial therapy should be active against pathogens most commonly involved in microbiologically documented and most threatening infections, including Pseudomonas aeruginosa, but excluding coagulase-negative staphylococci. In patients whose expected duration of neutropenia is more than 7 days and who do not respond to first-line antibacterial treatment, specifically in the absence of mold-active antifungal prophylaxis, further therapy should be directed also against fungi, in particular Aspergillus species. With regard to antimicrobial stewardship, treatment duration after defervescence in persistently neutropenic patients must be critically reconsidered and the choice of anti-infective agents adjusted to local epidemiology. This guideline updates recommendations for diagnosis and empirical therapy of fever of unknown origin in adult neutropenic cancer patients in light of the challenges of antimicrobial stewardship.
Published online: 30 August 2017
Gesehen am 21.06.2018